Etnotecnologia, Amazônia e culturais digitais - MOURA, Ricardo Damasceno (Universidade Federal do Pará, 2020)
The text approaches aspects of the cultural etnotecnologia as source of production of resources and social inclusion. Such vision in takes them to make an analysis of the technology as a phenomenon eminently contemporary, searching to lock up the elements that constitute it and they define it. After that we carry through a research on its proper distribution. We search to maper its definitions and its main theoretical matrices of analysis, as much in the scope politician, how much in the educational scope. Of ownership of these elements, we look for to identify as the technology interacts with the local culture and the sustentabilidade in the Amazon region. Finally, we search to more directly identify the assumed politics of digital inclusion for Brazil, in special in the Amazon. From then on, we establish a comparative boarding that in allowed to identify them the local specificities, to recognize the points of access and the difficulties of the distant localities, as well as identifying to the there existing identities in the present effort of construction of a new thought on bio-diverse patrimony and traditional knowledge.